‘Understanding the influence of microbial contamination on colour alteration of pigments used in wall paintings – The case of red and yellow ochres and ultramarine blue - Rosado, Tania (2020)
This article reports biocolonization assays carried out on yellow and red ochres and ultramarine blue pigments. These pigments have been most commonly used in traditional limewash of heritage buildings from southern Portugal (Alentejo) and, in the case of the yellow and red ochres, also in historical decorative wall paintings since Roman times. The research aim was to assess the potential role played by microorganisms in colour alterations observed in indoor and outdoor paint layers for conservation purposes.The assays accomplished several microorganisms previously isolated from degraded wall paintings with signs of biocontamination. The results show that apart from the clear physical stress induced in paint layers by the biometabolic activity, filamentous fungi, yeast, and bacteria are capable of inducing discoloration (in particular, the fungus Aspergillus niger). Raman analysis corroborates their active role in painting discolouration. This methodology, applied to bioprocesses, can be used as noninvasive methodology to signal microbial involvement.